Consumption of Fluoroethylene Carbonate (FEC) on Si-C Composite Electrodes for Li-Ion Batteries. Issue 8 (1st January 2016) - Jung, Roland; Metzger, Michael; Haering, Dominik; Solchenbach, Sophie; Marino, Cyril; Tsiouvaras, Nikolaos; Stinner, Christoph; Gasteiger, Hubert A.
Abstract : The electrolyte additive fluoroethylene carbonate (FEC) is known to significantly improve the lifetime of Li-ion batteries with silicon anodes. In this work, we show that FEC can indeed improve the lifetime of silicon-carbon composite anodes but is continuously consumed during electrochemical cycling. By the use of 19 F-NMR spectroscopy and charge/discharge cycling we demonstrate that FEC is only capable to stabilize the cell performance as long as FEC is still remaining in the cell. Its total consumption causes a significant increase of the cell polarization leading to a rapid capacity drop. We show with On-line Electrochemical Mass Spectrometry (OEMS) that the presence of FEC in the electrolyte prohibits the reduction of other electrolyte components almost entirely. Consequently, the cumulative irreversible capacity until the rapid capacity drop correlates linearly with the specific amount of FEC (in units of μmolFEC /mgelectrode ) in the cell. The latter quantity therefore determines the lifetime of silicon anodes rather than the concentration of FEC in the electrolyte. By correlating the cumulative irreversible capacity and the specific amount of FEC in the cell, we present an easy tool to predict how much cumulative irreversible capacity can be tolerated until all FEC will be consumed in either half-cells or full-cells. We further demonstrate that four electrons are consumed for the reduction of one FEC molecule and that one carbon dioxide molecule is released for every FEC molecule that is reduced. Using all information from this study and combining it with previous reports in literature, a new reductive decomposition mechanism for FEC is proposed yielding CO2, LiF, Li2 O, Li2 CO3, H2 and a partially cross-linked polymer.